Urban planning indicators: useful tools to measure the effect of urbanization and vegetation on summer air temperatures. (26th June 2013) - Petralli, Martina; Massetti, Luciano; Brandani, Giada; Orlandini, Simone
ABSTRACT In this article, the relationships between some urban planning indicators (GCR, green cover ratio; LCR, Lawn cover ratio; TCR, Tree cover ratio; SCR, street cover ratio; BCR, building cover ratio; BVD, Building volume density) and intra‐urban minimum and maximum average summer temperatures of Florence (Italy) were investigated. These indicators were calculated at different scales (areas of 10 m to 500 m radius) within the urban environment. Results showed that all the indicators can be used to assess the intra‐urban distribution of minimum air temperature values at all scales. Maximum air temperature was affected by GCR and TCR especially near the stations (radius up to 50 m), and by SCR at all scales, and the significance increased with radius. A 10% increase in LCR determined a reduction in minimum summer temperature from 0.14 °C (radius = 10 m; p < 0.05) to 0.53 °C (radius = 500 m; p < 0.01). A 10% increase in SCR determined an increase in minimum summer temperature from 0.22 °C (radius = 10 m; p < 0.01) to 0.66 °C (radius = 400 m; p < 0.01). The analysis of the type of green showed the significant role of forested areas on decreasing maximum temperatures and of grass areas on decreasing minimum temperatures. This research expands our scientific understanding of the effects of urban planning indicators on the intra‐urban thermal regime and can provide useful tools to urban planners and policymakers for the evaluation of the impact of an urban transformation on the thermal regime of the city at different scales.